La disgrafía y su incidencia en el aprendizaje de los estudiantes de segundo y tercer grado básico elemental de la Escuela “Consejo Provincial de Cotopaxi” periodo lectivo 2015-2016. Plan de capacitación. - Millingalli Oña, Rosario (2016)
This project aims to help the school community to solve the problem of dysgraphia, for this has been diagnosed factors influencing through technical writing, activities to develop motor skills and improve handwriting in children; taking into account that this difficulty occurs in children of normal intellectual capacity has to do with neurological problems but rather with other factors including: motor development of students. The central problem How dysgraphia affects the learning of students of second and third grade elementary Basic School "Provincial Council of Cotopaxi" 2014-2015 academic year? In seeking solutions you can participate, the entire school community to improve the learning process of children, and a better understanding quarterdeck reading writing has coherence and coordination. The main objective is to determine what degree of impact has dysgraphia in student learning second and third basic grade elementary, to establish the use of activities to optimize the development of academic activities of teachers and students for which was used the descriptive field research mode, the survey aimed at teachers and students in basic institution through the results an alternative proposal is presented as a training system for teachers `can present this problem in the most efficient manner. The research has a non-experimental model variables can not modify ie will work on the basis of what is observed without directly inferring that this practice in the School of Basic Education "Provincial Council of Cotopaxi".